IMPLEMENTASI KEBIJAKAN PENEMPATAN GURU SEKOLAH DASAR TERPENCIL DI KABUPATEN SINTANG - Benny Rustandi E.42008025 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
The title of this final task is implementation of isolate elementary school. Teacherplacing policy In sintang district. The purpose of this final task is to solve the problem that beenfaced by sintang government due to government policy by placing isolate elementary schoolteachers at sintang district. The problem formula of this research is how the implementationprocess by placing the teacher at isolate area. This research are use qualitative approaching anddescriptive method.The problem in appointing, placing and mutation elementary school teachers isolate inSintang regency, namely, the imbalanced spread of elementary school teachers between Sintangdistrict and Ketungau Hilir district, was the result from the inconsistent regulation inappointing, placing and mutation the teachers in the regency. This requires new regulation (localregulation) so that the BKD and local education office in Sintang regency has referential letter inimplementing the authorities.Keyword: implementation policy, placing isolate elementary school teacher.